Pengembangan Game Chem-Veryday untuk Meningkatkan Motivasi dan Hasil Belajar Peserta didik Kelas XI SMA Mengenai Faktor-Faktor yang Mempengaruhi Laju Reaksi dalam Kehidupan Sehari-Hari - Rahma Dani, Nafitria Nur; Lutfi, Achmad (UNIB Press, 2026)
This study aims to develop and examine the feasibility, practicality, and effectiveness of the Chem-Veryday educational game as a chemistry learning medium on the topic of factors affecting reaction rates for eleventh-grade senior high school students. This research employed a Research and Development (R&D) method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The research instruments included expert validation sheets, student response questionnaires, ARCS motivation questionnaires, and learning outcome tests in the form of pretests and posttests. The research subjects were eleventh-grade students of SMA Khadijah Surabaya. The validation results indicated that the Chem-Veryday game achieved a very high level of feasibility in terms of material accuracy, media design, and ease of use. The effectiveness test results showed a significant improvement in learning outcomes, with the average pretest score of 50.3 increasing to 94.8 in the posttest. The Wilcoxon Signed-Rank Test yielded a significance value of p < 0.001 with a very large effect size, indicating a strong impact of the Chem-Veryday game on students’ learning outcomes. In addition, students’ learning motivation increased across all ARCS components from low–moderate to very high levels. Student response results also demonstrated that the game is practical, engaging, and easy to use. Therefore, the Chem-Veryday educational game is considered valid, practical, and effective as a chemistry learning medium to enhance students’ motivation and learning outcomes on reaction rate material.